Performance evaluation of the Biosynex AMPLIQUICK Fecal Bacteriology PCR kit - Quentin Beaufils; Lucie Bénéjat; Astrid Ducournau; Johanna Aptel; Alicia Chevalier; Marine Jauvain; Philippe Lehours (BMC Microbiology)
Abstract This study assessed the clinical performance of the Biosynex AMPLIQUICK Fecal Bacteriology kit for detecting enteropathogenic bacteria in cases of acute community-acquired diarrhea. In total, 194 retrospectively collected and 207 prospectively collected stool samples were analyzed. In cases of discordant results between the AMPLIQUICK Fecal Bacteriology kit and initial status of the 401 stools, samples were reanalyzed using the Seegene Gastrointestinal Panel 1 and 2 kits or targeted PCR assays. Among the 401 samples, 190 were expected to be positive for Campylobacter spp. (C. jejuni or C. coli), 48 for Salmonella spp., 39 for Shigella spp./enteroinvasive Escherichia coli (EIEC), 21 for Yersinia enterocolitica, and 30 for enterohemorrhagic E. coli (EHEC). Additionally, 64 samples were expected to be negative. Nine other samples tested positive for either other enteropathogens (Aeromonas spp., Plesiomonas shigelloides, Vibrio spp., or Clostridioides difficile) or co-infections with two pathogens. Only three samples (four discrepancies) yielded discordant results with the AMPLIQUICK Fecal Bacteriology kit: one false positive for enterotoxigenic E. coli (ETEC), one false negative for EHEC, and one sample that was both falsely positive for Salmonella spp. and falsely negative for EHEC. The analytical performance was calculated using a composite reference standard (CRS) in the absence of a perfect gold standard. Due to the low number or absence of positive cases, the performance of the Biosynex AMPLIQUICK Fecal Bacteriology kit could not be determined for Vibrio spp., Yersinia pseudotuberculosis, hypervirulent C. difficile strains, Cholera toxin, ETEC, 0157 EHEC and P. shigelloides. Using this CRS, positive, negative and overall agreement rates ranged from 98.24 to 100% for all the other pathogens. In conclusion, the Biosynex AMPLIQUICK Fecal Bacteriology kit enables comprehensive screening for key bacterial pathogens associated with gastrointestinal infections in a single PCR assay. With excellent clinical performance, it represents a reliable tool for the rapid and accurate diagnosis of bacterial gastroenteritis in routine practice.